2011
DOI: 10.1371/journal.ppat.1002282
|View full text |Cite
|
Sign up to set email alerts
|

A Wide Extent of Inter-Strain Diversity in Virulent and Vaccine Strains of Alphaherpesviruses

Abstract: Alphaherpesviruses are widespread in the human population, and include herpes simplex virus 1 (HSV-1) and 2, and varicella zoster virus (VZV). These viral pathogens cause epithelial lesions, and then infect the nervous system to cause lifelong latency, reactivation, and spread. A related veterinary herpesvirus, pseudorabies (PRV), causes similar disease in livestock that result in significant economic losses. Vaccines developed for VZV and PRV serve as useful models for the development of an HSV-1 vaccine. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
147
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(153 citation statements)
references
References 186 publications
(233 reference statements)
3
147
0
3
Order By: Relevance
“…Thus, viral evolution can be discussed at the molecular level. Our analysis revealed that the nucleotide sequence similarity of US1 of PRV Becker to Kaplan and Bartha was 92 and 89% ( Figures 2A and 3A); the aa sequence similarities were up to 92 and 88%, respectively, consistent with a previous report (Szpara et al, 2011). Meanwhile, it may be that this evolutionary difference produces the variable virulence of distinct PRV strains.…”
Section: Discussionsupporting
confidence: 88%
“…Thus, viral evolution can be discussed at the molecular level. Our analysis revealed that the nucleotide sequence similarity of US1 of PRV Becker to Kaplan and Bartha was 92 and 89% ( Figures 2A and 3A); the aa sequence similarities were up to 92 and 88%, respectively, consistent with a previous report (Szpara et al, 2011). Meanwhile, it may be that this evolutionary difference produces the variable virulence of distinct PRV strains.…”
Section: Discussionsupporting
confidence: 88%
“…High‐throughput genome sequencing has provided evidence of recombination between strains in other herpesviruses, namely HSV‐2, VZV, Marek's disease virus, HSV‐1, pseudorabies virus, human cytomegalovirus and infectious laryngotracheitis virus (Hughes & Rivailler, 2007; Kolb, Larsen, Cuellar, & Brandt, 2015; Lee et al., 2013; Norberg et al., 2011, 2015; Sijmons et al., 2015; Szpara et al., 2014; Szpara, Tafuri, et al., 2011; Zell et al., 2012). In the present study, network analysis suggested that recombination has also occurred between EHV‐1 strains.…”
Section: Discussionmentioning
confidence: 99%
“…While Us9 is necessary for directly or indirectly interacting with KIF1A and recruiting the motor complex to transport vesicles, at least one additional viral protein that is missing or mutated in PRV Bartha is required for this interaction (6). The genome sequences of wild-type PRV Becker and Bartha have been completed (28). Compared to the 67 wild-type protein-coding regions, PRV Bartha has missense or silent mutations in at least 46 proteins as well as a deletion in the unique short region of the PRV genome that removes the coding sequences for gI (Us7), gE (Us8), Us9, and Us2.…”
Section: Both Ge and Gi But Not Us2 Are Required For Anterograde Spmentioning
confidence: 99%
“…KIF1A is necessary for anterograde axonal movement of viral particles, but at least one additional viral protein is required to facilitate or stabilize its interaction with Us9; this protein (or proteins) is not expressed by the attenuated PRV strain Bartha (6). The PRV Bartha genome contains multiple mutations compared to virulent PRV, including a deletion in the coding region for gI, gE, Us9, and Us2 (28). Since deletion of gE or gI severely reduces but does not completely disrupt the anterograde spread capacity of PRV in vitro (24), we hypothesized that these two proteins may be involved in the Us9-KIF1A interaction to promote virion transport.…”
mentioning
confidence: 99%